Modifikasi Circuit Training untuk Meningkatkan Keterampilan Bermain Futsal - Faisal Alfarisi; Ani Kurniawati; Z.Arifin (Mutiara Pendidikan dan Olahraga, 2025)
The popularity of futsal continues to increase among teenagers, but many players have not mastered basic skills and also lack physical abilities, which has an impact on playing skills on the field. This study aims to analyze the effect of circuit training modifications to improve futsal playing skills in futsal extracurricular students at SMA Negeri 19 Garut. The research method used was an experiment with a One group pre-test post-test design. The sample consisted of 20 students who were members of the SMAN 19 Garut futsal extracurricular. The instrument used was a futsal playing skills test using the General Performance Assessment Instrument (GPAI). The results showed an increase in the average general performance score with the results of the Asymp. (2-tailed) = 0.403 <α = 5% = 0.05 (significant). Based on these results, it can be concluded that circuit training modifications can improve futsal playing skills.